Directions for diversification of production in dekhkan farms - Samieva Tokhirovna, Gulnoza (THE INNOVATION ECONOMY, 2024)
Increasing the standard of living of the population by providing food, employment and the processing industry with agricultural raw materials is an important strategic goal of the economy. In the modern period of economic development, peasant farms, as the oldest organizational form of production, are of great importance in solving this strategic problem. Considering the relevance of the topic in the article, the development of proposals and recommendations aimed at the further development of farms in Uzbekistan, especially the Kashkadarya region, is of great scientific and practical importance, in order to ensure that part of the population is filled with work and income, and the market is filled with agricultural products through effective use of agricultural land. The article discusses the socio-economic essence, organizational and economic foundations, theoretical foundations of diversification and production efficiency, as well as issues of their development using foreign experience. It was also noted that diversification of production is an important factor in the further development of farms in the future, and studies of a number of foreign and domestic economists regarding the essence and effectiveness of the concept of diversification were